Essential C# 8.0, 7th Edition - Michaelis, Mark (Addison-Wesley Professional, 2020)
Essential C# 8.0 is a well-organized, no-fluff guide to C# 8.0 for programmers at all levels of experience. Reflecting the most important C# features, it will help you write code that's simple, powerful, robust, secure, and maintainable. Author Mark Michaelis is a world-class C# expert: a long-time Microsoft MVP and Regional Director who also has served on Microsoft's C# design review team. He presents a comprehensive tutorial and reference for the entire language, including expert coverage of key C# 8.0 enhancements. He illustrates key C# constructs with succinct examples, and presents best-practice coding guidelines.